The Biological and Economic Importance of Ice-Nucleating Bacteria (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2025)
Ice-nucleating proteins (INPs) located on the surface of ice-producing bacteria, particularly Pseudomonas syringae, are unique in their ability to induce ice formation at subfreezing temperatures. These proteins regulate the surrounding water molecules, accelerating ice crystal formation, which in turn damages crops through frost injury and leads to substantial agricultural and economic losses. According to studies such as those by Rupp et al., these bacteria actively contribute to ice development on plant surfaces, causing tissue destruction and reduced agricultural yields. Although their role in agriculture is harmful, they have been successfully exploited in several industries. For instance, Pseudomonas syringae is utilized in the production of artificial snow for skiing resorts and in industrial refrigeration, providing a sustainable alternative that enhances cooling efficiency and reduces energy consumption. Moreover, they play a crucial role in atmospheric processes by affecting cloud ice formation and precipitation, which has direct implications for the global water cycle. Research suggests that integrating INB into cloud systems may increase rainfall in drought-prone regions, potentially offering solutions to water scarcity. Furthermore, ice-producing bacteria are being investigated for pest management, plant resilience to cold stress, and soil fertility improvement. These diverse applications highlight their importance across agriculture, industry, and climate regulation, making them a subject of significant ongoing research.